The Force Between Two Sliding Bodies When Observed from a Third Moving Body - Don W. Perumean (Japanese Society of Tribologists, 2011)
This paper pertains to the observations of the sliding friction force from different moving bodies. The paper derives the equations required to predict the forces on the free-body diagrams of two sliding bodies when observed from a third moving body. The force equations were determined with the application of virtual work to determine system equilibrium. The results show that any sliding force equation including the classical Newtonian tractive equation must be multiplied by an intrinsic theoretical equation to obtain equilibrium on the isolated body when observed from a third moving body. This intrinsic equation is defined as the instantaneous percent sliding of the contact.